Court’s proceedings to secure claims in business lawsuits - Michór, Andrzej (Studia Iuridica Toruniensia, 2021)
This article’s aim is to discuss selected institutions of proceedings to secure claims in the context of the specific character of business lawsuits. Applications for securing claims in this type of cases are submitted to the courts quite often, especially in cases concerning the declaration of resolution’s invalidity or its annulment. On the other hand, the court’s ruling has far-reaching consequences for economic transactions.